Frequency of Faulty Inter-Proximal Contacts in Patients Receiving Fixed Dental Prosthesis (Medical Forum Monthly, 2022)
Objective: The objective of the study is to determine the frequency of faulty interproximal contacts in patients receiving fixed dental prosthesis.Study Design: Descriptive, cross sectional study.Place and Duration of Study: This study was conducted at the Prosthodontics Department, Bacha Khan Medical College Mardan from 17 October 2017 to 17 April 2018.Materials and Methods: Patients visiting the department of Prosthodontics, fulfilling the inclusion criteria was included in the study. Written informed consent was taken. Patients with porcelain fused to metal crowns and all metal crowns were assessed. The floss was passed through interproximal contacts under assessment. Proximal contact points were categorized as tight, open or loose and acceptable.Results: Out of the 174 participants (Male and Female) enrolled in this study, mean age of the patients was 35.2±7.9. Stratification analysis was performed and observed that the porcelain fused metal crown success rate being acceptable higher in all age group like 25-35 age grouped showed 59% acceptable rate and 36-45 years age group acceptance were 52%. The age is strongly associated with porcelain fused metal crown (P value 0.059) while gender was not associated with porcelain fused to metal crown (p vale 0.606).Conclusion: This study showed that majority of the fixed dental prosthesis and metal crown were acceptable. Too tight or loose dental prosthesis can have their own consequences. Therefore, it is suggested that the crown should be evaluated properly by the dentists; both clinically and radiographically before final cementation.